Emotional intelligence in victims of school bullying and in aggressors. (European Journal of Education and Psychology, 2010)
The purpose of this study was to analyze the relations between being the victim of school bullying and being the aggressor with the parameters associated with emotional intelligence (emotionality, efficacy, superstitious thinking, rigidity, esoteric thinking, illusion). The sample is made up of 248 students from 12 to 16 years of age, 144 male (58.1%) and 104 female (41.9%). To measure the variables, three assessment instruments were used: the Constructive Thinking Inventory, the My Life at School Checklist and the Antisocial-Delinquent Behavior Questionnaire. The results obtained confirmed that: 1) adolescents who had suffered many behaviors of intimidation or bullying, had a low level of emotional intelligence, low emotionality, low self-esteem, low frustration tolerance, low efficacy, and little activity; 2) the adolescents who had a high level of antisocial-delinquent behaviors showed a low level of emotional intelligence, low efficacy, low activity, low responsibility, and low tolerance. The discussion addresses the importance of implementing programs to promote emotional intelligence in order to prevent bullying at school.